Amazon Diversity: multiculturalism and the challenges of inclusive education in the Brazil-Colombia-Peru triple border (Research, Society and Development, 2022)
This paper aims to discuss about Amazonian Diversity and its relation with multiculturalism and inclusive education. Specifically, the issue of multiculturalism and the challenges of inclusive education in the Brazil-Colombia-Peru Tri-border area. It is understood that people with disabilities must be accepted and respected in their differences, limitations, needs and particularities, understanding that inclusion is not only about access to school and mere permanence in the classroom, but being aware of their rights of inclusion. The methodology of this article is bibliographic research, which consists of a collection of scientific productions on the theme, in order to present a historical and conceptual overview of the research issue under analysis. It was observed that the educational environment is of paramount importance to receive the students who need this inclusion, it is up to the teachers to prepare and adapt them to this multicultural reality for the exercise of diversity and surely the irreprehensible way salutary the manifestation of citizenship, character and legitimate respect, affection among others.